2019
DOI: 10.1037/prj0000326
|View full text |Cite
|
Sign up to set email alerts
|

Community mental health center staff attitudes about employment for persons with serious mental illness.

Abstract: To measure community mental health agency staff attitudes about employment for persons with serious mental illness. Methods: An online survey was developed and sent to 2,218 staff at 4 community mental health centers (CMHC) in 1 New England state. The survey collected quantitative and qualitative data about staff attitudes about employment for persons with serious mental illness. Descriptive statistics and qualitative results are provided. Results from analysis of variance are provided as well, assessing diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…Consequently, differing views between medical and social professionals may reduce the effectiveness of work rehabilitation programs, discouraging or confusing individuals who need to increase their intrinsic and extrinsic motivation to work (Reddy et al., 2016 ), which is a requirement for individuals to develop an active and action‐oriented attitude toward employment (Brantschen et al., 2017 ). This research also confirms other previous studies (Brucker & Doty, 2019 ; Fleming et al., 2019 ) and shows that medical mental health professionals may have a negative belief that people with mental illness cannot and do not want to work. The results also support literature showing how some mental health professionals may consider that work may hinder the recovery of people with mental illness (Casper & Carloni, 2007 ; Hamilton et al., 2013 ; Marwaha et al., 2009 ; Mueser & McGurk, 2014 ) since both psychiatrists and nurses give importance to frustration originated from work.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consequently, differing views between medical and social professionals may reduce the effectiveness of work rehabilitation programs, discouraging or confusing individuals who need to increase their intrinsic and extrinsic motivation to work (Reddy et al., 2016 ), which is a requirement for individuals to develop an active and action‐oriented attitude toward employment (Brantschen et al., 2017 ). This research also confirms other previous studies (Brucker & Doty, 2019 ; Fleming et al., 2019 ) and shows that medical mental health professionals may have a negative belief that people with mental illness cannot and do not want to work. The results also support literature showing how some mental health professionals may consider that work may hinder the recovery of people with mental illness (Casper & Carloni, 2007 ; Hamilton et al., 2013 ; Marwaha et al., 2009 ; Mueser & McGurk, 2014 ) since both psychiatrists and nurses give importance to frustration originated from work.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, another recent study showed that only half of professionals strongly agree that people with mental illness want work and, most importantly, around the same proportion moderately agree that people with mental illness cannot work (Brucker & Doty, 2019).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…This reflects the dominant implementation stance across the world where IPS is delivered by mental health services rather than PES’. The attitudes of health and social care staff has shown that they underestimate people with moderate to SMI' wishes to return to work and their capability to work, along with overestimating the risks connected to work related stress and fears of relapse (Boardman et al, 2003; Brucker & Doty, 2019; Marwaha et al, 2009). Training and exposure to IPS for health staff have been shown to result in more positive attitudes and behaviours towards supporting clients to gain and retain employment (Brucker & Doty, 2019; Craig et al, 2014; Rinaldi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As such, individual recipients of mental health care delivery should be given opportunities to participate in collaborative, interdisciplinary decision-making processes. Many vocational and clinical staff at CMHC have positive perceptions about the possibility of employing individuals who have experienced SPMD (Brucker & Doty, 2019). A person who was once a member of the SPMD community could be given the opportunity to assume the role of a stakeholder with the potential agency to address the multisystemic factors moderating consumers’ mental health.…”
Section: Micro Level: Social Justice Advocacy and Mental Health Consu...mentioning
confidence: 99%